2019
DOI: 10.11144/javeriana.upsy18-1.pfpb
|View full text |Cite
|
Sign up to set email alerts
|

Perfil financeiro dos psicólogos brasileiros: análise estatística relacionada ao ano de 2015

Abstract: La psicología brasileña ha revelado una tendencia creciente en su crecimiento. En 2013, una investigación llevada a cabo por el Consejo Federal mostró que Brasil tiene más de 250 000 profesionales con licencia, revelando 1.24 psicólogos por cada 1 000 habitantes. Sin embargo, faltan datos en la literatura sobre la información sobre el perfil financiero del psicólogo brasileño, que es el objetivo de este estudio. Dicho esto, esta investigación es un estudio exploratorio no probabilístico, tipo encuesta, realiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…On the one hand, models of career success are almost unanimous in taking financial gain as an elementary universe (Costa, 2013;Derr, 1986;Dries et al, 2008;Mayrhofer et al, 2016;Parker & Chusmir, 1992;Turban & Dougherty, 1994;Sutherland, 2017). It is also known that the financial factor is a fundamental aspect for the career of psychology professionals, although there are few studies that present in great detail the financial profile of Brazilian psychologists (Anunciação et al, 2019). In contrast, it is known that greater weight can be attributed to social recognition by clients and patients (Sobiraj et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, models of career success are almost unanimous in taking financial gain as an elementary universe (Costa, 2013;Derr, 1986;Dries et al, 2008;Mayrhofer et al, 2016;Parker & Chusmir, 1992;Turban & Dougherty, 1994;Sutherland, 2017). It is also known that the financial factor is a fundamental aspect for the career of psychology professionals, although there are few studies that present in great detail the financial profile of Brazilian psychologists (Anunciação et al, 2019). In contrast, it is known that greater weight can be attributed to social recognition by clients and patients (Sobiraj et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Brazil has 380,432 psychologists (Conselho Federal de Psicologia, 2020). A recent study aimed at outlining the profile of these professionals included a sample of 437 Brazilian psychologists (Anunciação et al, 2019). The results showed that the studied sample consisted of young people who worked in different areas in the domain of Psychology, had no other source of income and received an average monthly salary ranging from BRL 2,000.00 to BRL 3,000.00.…”
mentioning
confidence: 99%